The Effects of Comics on Second Language Vocabulary Development - Rizcallah, Yvette (2023)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Yvette Rizcallah entitled, “The Effects of Comics on Second Language Vocabulary Development”, submitted in November 2023. Thesis advisor is Dr. Ozgur Parlak. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).